Effectiveness of home-based, non-exercise interventions for dementia: A systematic review - Tan, Davynn Gim Hoon; Boo, Belinda Melody Bernadette; Chong, Cheyenne Shuen; Tan, Megan Michelle Ling-Li; Wong, Boon-Seng (Frontiers in Aging Neuroscience, 2022)
Introduction: Dementia is a neurodegenerative condition that is characterised by cognitive decline and increased functional dependency. With most persons living with dementia (PLWDs) residing at home, home-based interventions provide a convenient and individualised alternative for person-centred care. Most of the evidence focused on specific interventions or exercise-based activities; there remains a gap in understanding the impacts of a broader range of non-exercise interventions on PLWDs and their caregivers. This review aimed to understand the impacts of home-based, non-exercise interventions on the behavioural, functional, cognitive, and mood outcomes of PLWDs, and their caregiver’s quality of life (QoL), burden and mood. Methods: Search for studies published up to June 2021 were conducted on CINAHL, PsycArticles, PubMed, SAGE Journals, Science Direct, and Web of Science and using hand search. The inclusion criteria for the systematic review were: i) participants with a medical diagnosis of dementia, ii) participants who resided at own home, iii) intervention in the home setting, iv) investigate interventions other than physical exercise, v) randomised controlled trials (RCTs) or quasi-experimental studies, and vi) full-text study published in English and in a peer-reviewed journal. Results and Discussion: Eighteen studies consisting of 14 RCTs and 4 quasi-experimental studies were included. Interventions included were occupational therapy, cognitive rehabilitation, tailored activity program, cognitive stimulation therapy, personalised reminiscence, music therapy, reality orientation, biobehavioural and multicomponent interventions. Results were mixed, but important intervention features were highlighted. Personalised activities for PLWDs that are aligned to their interest and ability appeared to contribute to intervention effectiveness especially in reducing behavioral symptoms and improving functional status. Involvement of caregivers in interventions is another feature of effective interventions for both the PLWDs and the caregivers’ OoL, provided it is not deemed demanding or challenging to the caregivers. The inclusion of caregiver’s education was effective in reducing caregivers’ burden, particularly when the interventions are improving the PLWD’s functional status.